Zinc-Doped Titania Embedded on the Surface of Zirconia: A Potential Visible-Responsive Photocatalyst Material - Azizia Alifi; Rian Kurniawan; Akhmad Syoufian (Indonesian Journal of Chemistry, 2020)
The preparation and characterization of zirconia-supported titania with a zinc dopant had been studied. Zinc-doped titania was grown on the surface of zirconia by the sol-gel method. Various zinc contents and calcination temperatures were applied to investigate the zinc doping effect and crystal structure of the zirconia-titania composite. X-ray diffraction method, Fourier-transform infrared spectroscopy, and UV-Vis reflectance spectroscopy were performed to characterize the composite. The morphology of the composite was observed by using a scanning electron microscope, and its composition was analyzed by using energy dispersive spectroscopy. Among various zinc dopant contents and calcination temperatures investigated, doping with 5% zinc (Zn wt./Ti wt.) at 900 °C calcination shows the best result in response to visible light with a bandgap of 2.87 eV and absorption edge wavelength of 432.61 nm.